Parathyroid hormone linked to a collagen binding domain (PTH-CBD) promotes hair growth in a mouse model of chemotherapy-induced alopecia in a dose-dependent manner - Katikaneni, Ranjitha (Anticancer Drugs, 2014)
Chemotherapy-induced alopecia is a major source of psychological stress in patients undergoing cancer chemotherapy, and can influence treatment decisions. While there is currently no therapy, PTH-CBD, a fusion protein of parathyroid hormone and collagen binding domain, has shown promise in animal models. OBJECTIVE: To determine if there are dose-dependent effects of PTH-CBD on chemotherapy-induced alopecia in a mouse model. METHODS: C57BL/6J mice were waxed to synchronize hair follicles; treated on day 7 with vehicle or PTH-CBD (100, 320 and 1000 mcg/kg subcutaneous injection); treated on day 9 with vehicle or cyclophosphamide (150 mg/kg i.p.). Mice were photographed every 3–4 days and sacrificed on day 63 for histological analysis. Photographs were quantified by grey scale analysis to assess hair content. RESULTS: Mice not receiving chemotherapy showed regrowth of hair 2 weeks following waxing, and normal histology after 2 months. Mice receiving chemotherapy alone showed marked hair loss after chemotherapy, which was sustained for 10 days and was followed by rapid regrowth of a normal coat. Histology revealed rapid cycling dystrophic anagen/catagen follicles. Animals receiving chemotherapy and PTH-CBD showed decreased hair loss and more rapid regrowth of hair than that seen with chemotherapy alone (increased hair growth by grey scale analysis, p<0.05), and the effects were dose dependent. Histologically, hair follicles in animals receiving the highest dose of PTH-CBD were in a quiescent phase, similar to mice which did not receive chemotherapy. CONCLUSIONS: Single dose subcutaneous administration of PTH-CBD showed dose-dependent effects in minimizing hair loss and speeding recovery from chemotherapy-induced alopecia.